Hormone replacement therapy – the risks and complications - Bińkowska, Małgorzata (Menopause Review/Przegląd Menopauzalny, 2002)
There are many reasons why women take HRT. These include allevation of estrogen-deficiency symptoms, protection against cardiovascular disease, prevention of osteoporosis, a reduction of colon carcinoma, a reduction in the risk of developing Alzheimer's disease. However the compliance is generally poor. Adequate counseling is needed so the benefits can be balanced with the risks. The main risks include endometrial carcinoma, breast cancer and venous thromboembolic disease.